Sixth grade secrets - Sachar Louis 1954-; Louis Sachar (New York : Scholastic, 1987)
When Laura Sibbie starts a club called Pig City, she incites a near-war among her sixth-grade classmates and generates the creation of a rival club that has designs on Pig City's precious box of secrets.
H
520
H